(untitled) (Sustainability in Debate, 2021)
In 2015, the water crisis affecting the São Paulo Metropolitan Region reached its peak. The Federal Government published an Ordinance stablishing good practices in the management and use of water and electricity. This work aimed to verify if the management actions performed at the Universidade Federal de São Paulo were effective for water consumption reduction. It was analyzed secondary data of the monthly water consumption at campuses and Rectory, from 2014 to 2016. Statistical analyses were carried out comparing the water consumption between the periods pre- and post-intervention, which occurred in February 2015. The results show that the intervention reduced per capita water consumption by 33% in 2015 and 35% in 2016, saving up more than 65,000 m3 of water. These management actions were effective, and helped the academic population to achieve a more efficiently use of water and financial resources, becoming more sustainable.